Validity of Creative Interactive-Web and Seamless Learning Media and Learning Models to Improve Students' Creative Thinking Skills and Cognitive Learning Outcomes in High School Biology Subjects - Suharti, Dyah Istami; Tukiran; Raharjo (Postgraduate, University of Mataram, 2024)
This research aims to determine the validity of the Creative Interactive - Web And Seamless (CRI-WES) media and learning model. Development in this research uses the Wademan model which has five stages of development, namely problem identification, identification of tentative products and design principles, tentative products and theories, prototyping and initial product and theory assessment, and problem solving and theory development. The results of the biology education expert's validity analysis for content and construct validation showed a reliability percentage of 100% (R>75%). Biology education experts' validation of learning tools is included in the category of very valid, valid and sufficient to support learning with the CRI-WES model. Shows that the assessment tools and instruments are truly valid for use and do not require revision. This research produces an innovative learning model that is valid and can be used to assess practicality and effectiveness. This can also be applied to improve students' creative thinking abilities and cognitive learning outcomes in biology subjects at the high school level.